Frequencies of β-casein variants and their influence on genetic merit for production traits in Holstein cows - Caffaro, María Eugenia; Raschia, Maria Agustina; Maizon, Daniel Omar; Poli, Mario Andres (CSIRO Publishing, 2025)
Context: Traits considered for selection are influenced by social, consumer, and breeder demands. In the past decades, there has been increasing global interest in producing milk free from the β-casein (CSN2) A1 allele because of the health benefits it may have. This has encouraged many breeders to select A2A2 cows in their dairy cattle herds. Aims: This study aimed to evaluate the genetic variation in the bovine CSN2 gene regarding A1-like and A2-like variants and to assess the potential association between these variants and production traits in Holstein cows. Methods: In total, 2600 Holstein cows from three commercial dairy farms with different breeding objectives and phenotypic records taken over different seasons, periods, and lactations were genotyped for single-nucleotide polymorphism rs43703011, which distinguishes A1-like from A2-like β-casein variants. Allele and genotype frequencies were determined and their breeding values for milk, fat, and protein yields, and fat and protein percentages were estimated. The influence of CSN2 genotypes on these breeding values was studied through a one-way ANOVA. For the significant CSN2 genotype–breeding value associations, allele substitution effects were estimated. Key results: We found allele frequencies for A1-like and A2-like alleles in the ranges 0.262–0.366 and 0.634–0.738 respectively, and genotype frequencies in the ranges of 0.043–0.125, 0.43–0.537, and 0.393–0.523 for A1A1, A1A2 and A2A2 genotypes respectively. We demonstrated that the A2-like CSN2 variant correlates with higher estimated breeding values (EBVs) for milk, protein, and fat yields, and lower EBVs for fat and protein percentages. Conclusions: These results are valuable to visualize the trends in CSN2 allele and genotype frequency changes over the years and to analyze the effect of the different variants of β-casein on production performance. Implications: Our findings contribute to evaluating the consequences on dairy performance of selection for the A2-like variant.